PENGEMBANGAN APLIKASI MANAJEMEN KEUANGAN KOPERASI JATI HUSADA MULYA MENGGUNAKAN METODE FAST - Pratiwi, Cindhi; Hidayat, Ahmad Tri (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
The advancement of information technology in the era of globalization has transformed the operational practices of Savings and Loan Cooperatives (KSP), particularly in financial management. One of the main challenges faced by KSP is the reliance on manual methods for managing finances, which often leads to delays in producing accurate, comprehensive, and timely financial reports. These delays negatively impact decision-making, resulting in less optimal choices and potentially jeopardizing the sustainability of the business. This research aims to develop a technology-based financial management application to enhance efficiency, accuracy, and transparency in KSP's financial management. The application is designed using React for an interactive user interface and MongoDB NoSQL as the database for managing transaction and member data. The development process employs the Framework for the Application of System Thinking (FAST), tailored to meet the specific needs of the cooperative. The research findings indicate that this financial management application can improve KSP's financial performance, support better decision-making, increase transparency for members, and facilitate data management. Thus, the application contributes to the sustainable growth of KSP and the well-being of its members.